2003
DOI: 10.1046/j.1471-4159.2003.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Marked disparity between age‐related changes in dopamine and other presynaptic dopaminergic markers in human striatum

Abstract: Because age-related changes in brain dopaminergic innervation are assumed to influence human disorders involving dopamine (DA), we measured the levels of several presynpatic DAergic markers [DA, homovanillic acid, tyrosine hydroxylase (TH), aromatic L-amino acid decarboxylase (AADC), vesicular monoamine transporter 2 (VMAT2), and dopamine transporter (DAT)] in post-mortem human striatum (caudate and putamen) from 56 neurologically normal subjects aged 1 day to 103 years. Striatal DA levels exhibited pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
138
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(154 citation statements)
references
References 74 publications
15
138
0
1
Order By: Relevance
“…The lack of an aging change of VMAT2 protein in the nigrostriatal system in our limited sample size and within a limited age span is nonetheless consistent with a previous Western blotting study (Haycock et al, 2003) and a recent PET VMAT2 imaging report (Troiano et al, 2010) although the question of the influence of aging on striatal VMAT2 in the human is still controversial (cf. Troiano et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The lack of an aging change of VMAT2 protein in the nigrostriatal system in our limited sample size and within a limited age span is nonetheless consistent with a previous Western blotting study (Haycock et al, 2003) and a recent PET VMAT2 imaging report (Troiano et al, 2010) although the question of the influence of aging on striatal VMAT2 in the human is still controversial (cf. Troiano et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…As expected (Haycock et al, 2003), the antibody detected in human striatal samples a total of four broad protein bands with an MW of B75 (I), 55 (IIa), 45 (III), and 35 kDa (IV), respectively ( Figure 1A). The B75 kDa VMAT2 I was the predominant band, accounting for 53% ± 2% (n = 10) and 56% ± 3% (n = 10) of the total VMAT2 immunoreactivity in putamen and caudate, respectively.…”
Section: Characterization Of Vesicular Monoamine Transporter 2-immunosupporting
confidence: 79%
See 1 more Smart Citation
“…These observations are not surprising as the presence or absence of sex hormones is only one factor that could affect behavioral responsiveness to stimulants across adolescence. Forebrain dopamine systems continue to mature and reorganize across adolescence (Haycock et al 2003;Montague et al 1999;Teicher et al 1995;reviewed in Spear 2000). For example, it has been shown that there is an overproduction and regressive pruning of striatal dopamine receptors during adolescence (Teicher et al 1995).…”
Section: : Discussionmentioning
confidence: 99%
“…The multiple factor framework proposes "distinct age-associated cascades that target different brain systems and may independently vary in their level of progression across individuals" (in Buckner, 2004, p. 196). Investigators have given particular attention to frontalstriatal white matter changes (Salat et al, 2005), frontal gray (Raz et al, 1997;Salat et al, 1999) and striatal volume loss (Raz et al, 2003), and neuro-chemical changes such as reduction of dopamine (Haycock et al, 2003). Typically, researchers refer to age ranges starting at 65 and older as a particularly vulnerable period for expression of specifically age associated pathophysiological changes (Buckner, 2004).…”
Section: Introductionmentioning
confidence: 99%